1991
DOI: 10.3801/iafss.fss.3-585
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Oxygen Concentration On Co And Smoke Produced By Flames

Abstract: A modified cone calorimeter with an enclosure has been developed for measuring the yield of combustion products including CO and smoke under vitiated conditions. The CO yields of methane, propane, PMMA, ABS, polyethylene, and Douglas fir are found to increase by at least a factor of two as the oxygen concentration is decreased from 21% to 14%, while the smoke yields are found to be insensitive to vitiation for the solid materials (less than 30% change).Results for air vitiated separately by nitrogen and by car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…Fully ventilated combustion data show that CO and soot emissions are correlated and the ratio of their emission rates (or yields) is a constant [2][3][4][5][6][7][8][9][10]. It is thus suggested that there is a similarity between the kinetic and air-fuel mixing processes that govern the formation and oxidation of both CO and soot [5,7,8].…”
Section: Superscriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fully ventilated combustion data show that CO and soot emissions are correlated and the ratio of their emission rates (or yields) is a constant [2][3][4][5][6][7][8][9][10]. It is thus suggested that there is a similarity between the kinetic and air-fuel mixing processes that govern the formation and oxidation of both CO and soot [5,7,8].…”
Section: Superscriptsmentioning
confidence: 99%
“…It is generally accepted that CO and soot compete for free radicals, especially OH and O and thus their formation and emission depend on the availability of free radicals [2][3][4][5][6][7][8][9]. The following overall kinetics for the soot and CO emission has been suggested [2]:…”
Section: Superscriptsmentioning
confidence: 99%
“…There are two factors that can affect the CO production in compartment fires, ventilation and vitiation [2]. With respect to the effect of ventilation, extensive investigation has been done on compartment fires [3] and laminar jet diffusion flames [4] in the normal oxygen concentration condition.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements are performed with a 64 kg.m -3 ceramic fibre insulation pad on the backside of the sample as specified in the ISO 5660-1 standard [5]. During these experiments, the volumetric flow rate of the extraction through the exhaust duct of the calorimeter E v  is set at (24 ± 2) dm 3 …”
Section: Experimental Procedures and Conditionsmentioning
confidence: 99%
“…For more than two decades, the reaction-to-fire of materials has mainly been studied with bench scale experiments to control the test conditions. The most important bench-scale instruments for fire testing are the cone calorimeter (standard and equipped with a controlled atmosphere enclosure) [1][2][3][4] and the fire propagation apparatus (FPA) [5], which were developed in the early 1980s. Over the years, these devices have allowed great progress and a better understanding of the physical phenomena occurring when materials burn in well-ventilated conditions.…”
Section: Introductionmentioning
confidence: 99%